Interviewing Álvaro Marchesi. (Journal of Parents and Teachers, 2014)
In this article, Alvaro Marchesi is interviewed, one of the greatest references in Evolutionary Psychology in our country, who talks about LOGSE, his errors and successes, the LOE, and comments on school failure.
Keywords: Interview; Álvaro Marchesi; LOGSE; LOE.